Biostimulant activity of silicate compounds and antagonistic bacteria on physiological growth enhancement and resistance of banana to Fusarium wilt disease - Zakaria, Md Aiman Takrim; Sakimin, Siti Zaharah; Ismail, Mohd Razi; Ahmad, Khairulmazmi; Kasim, Susilawati; Baghdadi, Ali (Multidisciplinary Digital Publishing Institute, 2023)
Biostimulants such as silicate (SiO3 2ˆ’) compounds and antagonistic bacteria can alter soil microbial communities and enhance plant resistance to the pathogens and Fusarium oxysporum f. sp. cubense (FOC), the causal agent of Fusarium wilt disease in bananas. A study was conducted to investigate the biostimulating effects of SiO3 2ˆ’ compounds and antagonistic bacteria on plant growth and resistance of the banana to Fusarium wilt disease. Two separate experiments with a similar experimental setup were conducted at the University of Putra Malaysia (UPM), Selangor. Both experiments were arranged in a split-plot randomized complete block design (RCBD) with four replicates. SiO3 2ˆ’ compounds were prepared at a constant concentration of 1. Potassium silicate (K2SiO3 ) was applied on soil uninoculated with FOC, and sodium silicate (Na2SiO3 ) was applied to FOC-contaminated soil before integrating with antagonistic bacteria; without Bacillus spp. ((0B)”control), Bacillus subtilis (BS), and Bacillus thuringiensis (BT). Four levels of application volume of SiO3 2ˆ’ compounds 0, 20, 40, 60 mL) were used. Results showed that the integration of SiO3 2ˆ’ compounds with BS (108 CFU mLˆ’1 ) enhanced the physiological growth performance of bananas. Soil application of 28.86 mL of K2SiO3 with BS enhanced the height of the pseudo-stem by 27.91 cm. Application of Na2SiO3 and BS significantly reduced the Fusarium wilt incidence in bananas by 56.25%. However, it was recommended that infected roots of bananas should be treated with 17.36 mL of Na2SiO3 with BS to stimulate better growth performance.